Budget Cuts as Welfare Reform - Danziger, Sheldon (American Economic Review, 1983)
President Nixon's 1969 proposal for a Family Assistance Plan (FAP) established welfare reform as a major social policy goal. In his first year in office, President Carter also placed welfare reform-the Program for Better Jobs and Income (PBJI)-high on his legislative agenda. The FAP and PBJI were both variants of the negative income tax. They shared several common elements, including a national minimum income guarantee, an extension of benefits to persons who were categorically ineligible under existing programs, a concern with maintaining work incentives by keeping marginal benefit reduction rates on earnings well below 100 percent, and a belief that a reformed welfare system could control the growth in costs and case loads. Both also generated fatal political opposition and harsh criticism from welfare analysts who pointed out that the triangle-the tradeoffs among income guarantees, work incentives, and total costs-made their goals mutually inconsistent. President Reagan also placed welfare reform at the center of his social policy agenda in his first year in office. Unlike his predecessors' plans, his reform was successful. By October 1981, a drastic fiscal retrenchment had been proposed, legislated, and implemented in the largest cash welfare program, Aid to Families with Dependent Children (AFDC). The Reagan reform, incorporated in the Omnibus Budget Reconciliation Act of 1981 (OBRA), does not confront the iron triangle of negative income tax plans like FAP or PBJI. It does not attempt to reduce poverty by altering income guarantees or extending eligibility. It does not attempt to encourage work effort by lowering marginal tax rates on recipients. Supply-side logic notwithstanding, it reduces costs and case loads by raising the tax rate on welfare recipients' earnings to 100 percent and by establishing more restrictive gross income limits. President Reagan has reformed welfare by cutting the budget. He has clearly reduced welfare dependency in the short run, as the number of AFDC recipients has declined in most states by between 10 and 15 percent in the last year. A complete evaluation of the long-run effects of the OBRA reforms on the economic well-being and work effort of welfare recipients must await data on behavioral responses that have only recently been induced. Nonetheless, an analysis of the redistributive effects of welfare in recent years can provide a basis for estimating how reduced welfare dependency will affect economic well-being in the short run.